2003
DOI: 10.1089/153056203763317747
|View full text |Cite
|
Sign up to set email alerts
|

TIMTEM Project: Our Experience in a Remote Area

Abstract: We report our experience, begun in 1998 on a small island in the Dodecanese area of Greece, which has been called TIMTEM. The aim of this project was to improve care for people living on islands, creating a model exportable to other rural areas. The operative setting of the TIMTEM project is the island of Tilos (Greece); local authorities take part in it under the guidance of the only physician available on the island. The University of Pisa-Italy (Department of Surgery, Post-graduate School of Emergency Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Some of the earliest research projects using clinical telesonography were applied to subspecialties such as cardiology and obstetrics 7 . Although early projects were limited by the transmission bandwidth and signal degradation, early successes with transmitted echocardiograms and fetal scans have spurred continued interest and research in counties and continents such as Canada, Great Britain, Europe, and Australia 4 6 , 8 , 9 . Within the past decade, several studies have shown the clinical feasibility and patient and physician acceptance of telesonography systems to provide care to remote populations.…”
Section: Historical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the earliest research projects using clinical telesonography were applied to subspecialties such as cardiology and obstetrics 7 . Although early projects were limited by the transmission bandwidth and signal degradation, early successes with transmitted echocardiograms and fetal scans have spurred continued interest and research in counties and continents such as Canada, Great Britain, Europe, and Australia 4 6 , 8 , 9 . Within the past decade, several studies have shown the clinical feasibility and patient and physician acceptance of telesonography systems to provide care to remote populations.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Most telesonography research focuses on its use within an ambulatory care setting with a continued emphasis on obstetric imaging 14 , 21 , 22 ; however, infectious disease applications, 23 , 24 nonobstetric transabdominal scans, 3 musculoskeletal scans, 25 FAST scans, 6 , 26 and even the use of a robotic arm to perform scans 27 have also been explored. In addition to telesonography, many studies have proven the effectiveness of store‐and‐forward telemedicine, including such fields as dermatology, 28 dentistry, 29 and neurology, 30 including several projects based in developing nations 31 33 …”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telesonography networks experimentally developed to follow the principle of "fulfillment of needs", were designed for assessment and monitoring of certain isolated communities or certain pathologies. Therefore, projects were carried out on the islands [17][18], on ships [19], on remote locations or even in space [20][21][22].…”
Section: Telesonography -The 5th Dimension Of Ultrasound Examinationmentioning
confidence: 99%
“…Teledermatology is and has been practised in many parts of the world, including Norway, Finland, the USA, Canada, Australia, New Zealand, Northern Ireland, the Marshall Islands and the Greek island of Tilos. 4,5,6,7,8,9 Telemedicine services have broadly evolved into two categories: store and forward telemedicine, and synchronous or real-time telemedicine. Store and forward telemedicine, as its name implies, involves forwarding information which has already been saved in an electronic format to a consultant who reviews the case in his or her own time.…”
Section: Introductionmentioning
confidence: 99%